Factors Affecting Online Impulse Buying Behavior of Fashion Products on Live: Instagram Vs Tiktok - Gabriella Olivia Kristi; Daniel Tumpal H. Aruan (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2023)
This study analyses the influence of these factors and their underlying motivations. This research model is based on the stimulus organism response framework (S-O-R) to explore consumer reactions and behavior after certain stimulus factors. A measurement model was created based on valid responses from online questionnaires with the help of Structural Equation Modelling (SEM) using Smart-PLS. This study uses quantitative methods. The sampling technique used in this study was purposive sampling with the aim of ensuring that the respondents met the study's criteria. so that the number of samples in this study was 400 Instagram or TikTok users. The research results show that Attractiveness and expertise affect perceived enjoyment in buying online fashion products on live Instagram and TikTok positively and significantly. Product usefulness, purchase convenience, and product price affect perceived usefulness in buying online fashion products on live Instagram and TikTok positively and significantly. usefulness positively and significantly affected perceived enjoyment in buying online fashion products on live Instagram and TikTok. Perceived enjoyment and perceived usefulness mediate the urge to buy impulsively in buying online fashion products on live Instagram and TikTok positively and significantly. Trustworthiness is proven to have no positive or significant effect on the perceived enjoyment of buying online fashion products on live Instagram and TikTok.